Предмет: Алгебра,
автор: li2li2ya32
упростите выражение 4√2х-√32х+√2х
Ответы
Автор ответа:
1
√16*2х - √ 32х + √ 2х= √ 32х-√ 32х + √ 2х= √2х
Автор ответа:
0
4√2х-√32х+√2х=4√2х-√16*2х+√2х=
=4√2х-4√2х+√2х=√2х
(3х-5)-(7-4х)=2
3х-5-7+4х=2
7х-12=2
7х=2+12
7х=14
х=14:7
х=2
=4√2х-4√2х+√2х=√2х
(3х-5)-(7-4х)=2
3х-5-7+4х=2
7х-12=2
7х=2+12
7х=14
х=14:7
х=2
li2li2ya32:
решите уравнение (3х-5)-(7-4х)=2
Похожие вопросы
Предмет: Математика,
автор: oksanaloseva8
Предмет: Литература,
автор: Аноним
Предмет: Английский язык,
автор: Schanka
Предмет: Русский язык,
автор: minicoticicnigi
Предмет: Английский язык,
автор: kazybaeva2006